Performance investigation of parabolic trough solar receiver. (25th February 2016) - Guo, Jiangfeng; Huai, Xiulan; Liu, Zhigang
Highlights: There exists an optimal mass flow rate for exergy efficiency. The appropriate evaluation criterion has crucial effect on optimization. The optical heat loss far outweighs the heat loss of solar receiver. The exergy lost from receiver ends dominates in all exergy losses. Abstract: The influences of some parameters on the performance of parabolic trough solar receiver are investigated in the present work. When the mass flow rate of working fluid, ambient temperature and solar incident angle increase, the heat losses of solar receiver decrease. The exergy losses of solar receiver increase as the inlet temperature of working fluid, wind velocity, and the inner diameter of glass cover increase. The convective heat loss of glass cover predominates in the heat losses of solar receiver based on thermal efficiency, but the exergy lost from absorber ends takes the largest proportion. The optical heat loss of solar collector is far more than the heat losses of solar receiver, especially in the larger solar incident angle. There exists an optimal mass flow rate of working fluid for exergy efficiency, and the thermal efficiency and exergy efficiency have opposite changing tendencies under some conditions. Therefore, the selection of evaluation criteria is crucial to the performance optimization of solar collector system. This study is of great significance to guide the design and optimization of parabolic trough receivers.